Enhancing reading speed: the reading acceleration effect in Italian adult readers - Zamfira, Denisa Adina; Di Dona, Giuseppe; Battista, Martina; De Benedetto, Francesco; Ronconi, Luca (Frontiers in Psychology, 2024)
Introduction Enhancing reading efficiency is of paramount importance in various academic, professional and clinical domains. Previous research, mostly from a single laboratory, has shown that externally imposed time constraints by means of text fading can enhance reading fluency in children and adults with varying reading abilities and in different languages. Methods In the present study, we aimed at replicating and extending previous results in Italian readers. Three experiments (N = 90) were conducted: (i) to investigate the effects of continuous fading compared to character-wise fading, (ii) to investigate the influence of enlarged inter-letter spacing on reading acceleration outcomes, and (iii) to probe whether reading gains can be reliably observed off-line (after the acceleration) by comparing accelerated reading with an analog non-accelerated procedure. Results Overall, results corroborate previous findings revealing that participants read 40% faster during the reading acceleration procedure, while maintaining the same accuracy levels. Continuous fading proved to be more effective than character-wise fading in enhancing reading speed, while larger inter-letter spacing did not significantly affect the reading speed gain. Albeit the non-clinical nature of our sample and its numerosity circumscribe the potential generalization, taking into account individual differences in the initial reading time, data suggests that reading acceleration leads to larger off-line speed increments with respect to non-accelerated reading. Discussion Taken together, these findings offer valuable insights for the future application of reading acceleration procedures as part of multisession training programs for improving reading proficiency in a diverse range of clinical and non-clinical populations.